Engaged leadership : building a culture to overcome employee disengagement - Swindall, Clint, 1967- (Hoboken, N.J. : John Wiley, 2011)
'Engaged Leadership 2e addresses the challenge of employee disengagement. Great leaders realize that in order to thrive, they must overcome the epidemic of employee disengagement. Building a culture to overcome employee disengagement is even more important now than it was three years ago. When times were great, it was rather easy for leaders to overlook disengaged employees as long as the business was growing and numbers were being met. With smaller teams to perform the work, it is essential that employers get the most from employees by ensuring a culture of engagement. As we emerge from the recession and businesses begin to hire again, employees will have options they haven't had in a few years. Employers may begin to see their best and brightest depart for other opportunities if a culture of disengagement has been allowed to exist. It will be imperative for leaders to focus on employee engagement in order to encourage good employees to stay when other opportunities arise, and to attract top talent when hiring resumes. Engaged Leadership 2e will provide even more reasons for building a culture to overcome employee disengagement. Clint will address the impact high unemployment has had on employee engagement, and the impact it has had on those left behind doing the work of two people. He will also address the issues surrounding a lack of job security brought on by the global recession, and the growing impact of social media on employee engagement. And finally, Clint will update the fable to make it more current, and will add on additional sections to update readers on where certain characters have ended up as a result of the current economic impact on the organization in the fable. He will also tie the updated fable to closely to Living for the Weekday, with the ultimate goal of tying the two books together in all his speaking and consulting'--
Keywords: Leadership; Employee motivation; BUSINESS & ECONOMICS / Leadership